2015
DOI: 10.1111/mec.13384
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter quantity and quality shape microbial community compositions of subtropical broadleaved forests

Abstract: As two major forest types in the subtropics, broadleaved evergreen and broadleaved deciduous forests have long interested ecologists. However, little is known about their belowground ecosystems despite their ecological importance in driving biogeochemical cycling. Here, we used Illumina MiSeq sequencing targeting 16S rRNA gene and a microarray named GeoChip targeting functional genes to analyse microbial communities in broadleaved evergreen and deciduous forest soils of Shennongjia Mountain of Central China, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 58 publications
7
64
0
Order By: Relevance
“…Interestingly, Ding, et al . 25 , also found that the soil bacterial network of a broadleaved evergreen forest presented a higher resistance to environmental changes than that of a broadleaved deciduous forest. On the other hand, we discovered that most of the OTUs identified as module hubs and connectors (generalists) by the Zi-Pi plot (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Interestingly, Ding, et al . 25 , also found that the soil bacterial network of a broadleaved evergreen forest presented a higher resistance to environmental changes than that of a broadleaved deciduous forest. On the other hand, we discovered that most of the OTUs identified as module hubs and connectors (generalists) by the Zi-Pi plot (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…48 , comparing the soil microbial communities of a natural mature forest with those of a natural secondary forest, found a strong positive correlation between the soil bacterial community structure and the GeoChip-based functional community composition. However, there are other studies showing no significant correlations between microbial taxonomic and functional composition 25, 39 , which is explained as a consequence of the functional redundancy of soil microbial communities 49 . The contradictory results may be caused by differences in terms of techniques, scale or ecosystem investigated 22 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…3 The network of the forest soil bacteria. National Nature Reserve (Ding et al 2015). However, broadleaved forestry soil contained more Actinobacteria hubs, known as copiotrophic bacteria preferentially living in abundant resources (Ramirez et al 2012), suggesting that the key species of soil can be disparate in different forestry ecosystem.…”
Section: Composition Of Soil Bacterial Communitymentioning
confidence: 99%